New regional development concepts for rural peripheries: The case of the Scottish Highlands & Islands - Mose, Ingo; Brodda, Yvonne (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
The Scottish Highlands and Islands have been classified as one of the classic rural peripheries within Europe for a long time. Against this background the paper summarizes the historical development and the process of marginalisation the Highlands and Islands have experienced, in particular describing the regional policy measures applied over the last 40 years. Further focus lies on the current discussion of so called integrated rural development concepts that form the core of a more general reform of concepts, programmes and instruments in Scottish regional policy.